Epidemiology of synchronous and metachronous type multiple primary neoplasms - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
Multiple primary neoplasms (MPNs) comprise synchronous or metachronous tumors. They arise after diagnosis of the first primary tumor, and are commonly reported with an incidence of 0.7% to 11.7% of all cancer patients. By appropriate statistical methods, these tumors are shown to occur more frequently than expected, and therefore, may provide a model for generating and testing hypotheses on mechanisms of carcinogenesis. Some studies suggest that men are more frequent than women to develop both synchronous and metachronous tumors. Despite the controversial reports about the age of onset for MPNs, the consensus is that the mean age of developing MPNs at first diagnosis is high, such that many patients with MPNs are over 50 years. However, the risk of developing multiple cancers after the first primary for cancers like those of the thyroid increases for patients younger than 40 years of age. The mean age at diagnosis for synchronous and metachronous tumors do not differ significantly. Generally, the same organ or systems are involved. For instant MPN of the respiratory, gastrointestinal, and genitourinary systems are common. Most of the studies look for the association between MPNs and a specific system or organ such as the gastrointestinal, breast, head and neck, thyroid or brain. On the other hand, there are different definitions for MPNs and also the discrepancy in classifications and coding for reporting make comparisons difficult. Hence, in order to interpret the discordance and decrease the bias on this issue, it is highly recommended for researchers to use the international rules in their national registries. © 2011 by Nova Science Publishers, Inc. All rights reserved.